High-performance three-phase PWM converter with a reduced dc-link capacitor under unbalanced AC voltage conditions - Ren, Chunguang (2020)
Personal use is permitted, but republication/redistribution requires IEEE permission. A high-performance three-phase pulse width modulation (PWM) converter with reduced dc-link capacitor under unbalanced ac voltage conditions is proposed in this paper. The unique feature of the converter lies in that sinusoidal symmetrical ac currents and ripple free dc voltage can be achieved simultaneously without using a bulky capacitor, which was thought to be a dilemma in the past. The control scheme is implemented in an α-β frame, so the complex rotate transformations are avoided, and it does not require the extraction of positive and negative sequence currents, which simplifies the control algorithm. A two-quadrant operation active power compensator together with its controller is developed to suppress the voltage ripple in the dc-link. Compared with the passive compensation method, the compensator is equipped with a smaller capacitor to reduce the system size, weight, and cost. Moreover, the compensator could be integrated with the conventional three-phase three-leg PWM converter seamlessly. The effectiveness of the proposed control schemes is verified by the experiment results.